Functional Morphometric Analysis in Cellular Behaviors: Shape and Size Matter. Issue 9 (27th May 2013) - Yu, Haiyang; Lim, Kee Pah; Xiong, Sijing; Tan, Lay Poh; Shim, Winston
Abstract Cellular morphogenesis in response to biophysical and topographical cues provides insights into cytoskeletal status, biointerface communications, and phenotypic adaptations in an incessant signaling feedback that governs cellular fate. Morphometric characterization is an important element in the study of the dynamic cellular behaviors, in their interactive response to environmental influence exerted by culture system. They collectively serve to reflect cellular proliferation, migration, and differentiation, which may serve as prognostic indices for clinical and pathological diagnosis. Various parameters are proposed to categorize morphological adaptations in relation to cellular function. In this review, the underlying principles, assumptions, and limitations of morphological characterizations are discussed. The significance, challenges, and implications of quantitative morphometric characterization of cell shapes and sizes in determining cellular functions are discussed.